Nest architecture of Atta laevigata (F. Smith, 1858) (Hymenoptera : Formicidae) - Moreira, A. A.; Forti, Luiz Carlos [UNESP]; Andrade, APP; Boaretto, MAC; Lopes, JFS (Swets Zeitlinger Publishers, 2004)
The internal structure of three nests of Atta laevigata was studied in Botucatu city, São Paulo State, Brazil. Two nests were excavated through the opening of trenches and one was cement-moulded to enable a better view of the internal structures. The three nests presented a similar structure, with the depths and number of chambers varying as a function of the loose soil area of the nests. The number of chambers ranged from 1149 to 7864, reaching as deep as 7 m underground. Chamber volume ranged from 0.03 to 511. The foraging tunnels extended as far as 70m from the loose soil region. The nests of this species are the deepest within the genus Atta and have the highest number of chambers.
Keywords: Atta laevigata; nest architecture; internal structure